Environmental and health risk assessment of heavy metal contamination in rice from Gashua, Yobe State, Nigeria - Yerima Gwamna; M. Y. Kabiru; S. M. Abdullahi; A. Aji; C. D. Zakaria; S. A. Abdullaziz; B. K. Bello; J. Yerima; S. D. Chabiri; A. Goni; G. Chamba; S. Hamman (Indonesian Journal of Applied Environmental Studies, 2025)
This study investigates heavy metal contamination in rice from Gashua, Yobe State, Nigeria—an important rice-producing area potentially affected by environmental pollution. Given the widespread consumption of rice as a dietary staple and the rising prevalence of kidney-related diseases in the region, the research aimed to quantify the concentrations of arsenic (As), cadmium (Cd), lead (Pb), and chromium (Cr) in rice and assess their associated health risks. Using a simple random sampling technique, 120 rice samples were collected, consisting of 90 paddy rice from four farms and 30 parboiled rice from Gashua Market. Samples were digested and analyzed using Microwave Plasma–Atomic Emission Spectrometry (MP-AES), and data were evaluated through one-way analysis of variance (ANOVA). The results showed a significant (P<0.05) variation in heavy metal concentrations among samples. Parboiled rice from Gashua Market contained the highest arsenic level (0.383 mg/kg), exceeding WHO and USEPA limits. Cadmium (0.0242 mg/kg) and lead (0.102 mg/kg) also surpassed permissible limits of 0.001 mg/kg and 0.0035 mg/kg, respectively. Hazard Quotient (HQ) values for children indicated low risk, with all values below the threshold of 1. However, in adults, the HQ value for chromium at Gashua Market (2.162) exceeded the safe limit, suggesting potential health risks. The Hazard Index (HI) for both adults and children was greater than 1, primarily due to elevated concentrations of arsenic and chromium, signaling possible non-carcinogenic effects. Incremental Lifetime Cancer Risk (ILCR) analysis further indicated an increased risk of cancer from prolonged exposure. In conclusion, rice grown and sold in Gashua is contaminated with heavy metals at levels posing both carcinogenic and non-carcinogenic health risks. These findings underscore the urgent need for continuous monitoring, stricter regulatory enforcement by agencies such as NAFDAC, and proactive public health interventions to ensure food safety and protect community health.